A expansão do mercado imobiliário em Mossoró: acumulação capitalista e o aprofundamento das contradições socioespaciais - Nascimento, Eduardo Alexandre do (2013)
The housing market in Mossoró Rio Grande do Norte (RN) - Brazil have expanded at present moment, causing important changes in the economy and altering the configuration of urban space in the city. However, the effects of this process adversely affect the poor population of the city, creating a series of social problems. This process becomes still more contradictory with the presence of the Programa Minha Casa Minha Vida Program My House My Life (PMCMV). Although this program has to a central purpose (at least in theory) of solve part of the problem of housing scarcity in the country, in the practice its closely links to the logic of capital, stimulates the housing market, cooperating to increased speculation, contributing thus for the more expensive valor of urban land and buildings, putting up as an impediment to the poor population to access to homeownership and decent housing. In this perspective, this paper investigates the nature of the current process of expanding of housing market, animated largely by funds from the PMCMV, and its implications on the social and spatial dynamics of Mossoró, focusing especially the deepening of urban crisis and the contradictions of urban space in this city